2020
DOI: 10.3390/ijms21165696
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant CXCR4 Signaling at Crossroad of WHIM Syndrome and Waldenstrom’s Macroglobulinemia

Abstract: Given its pleiotropic functions, including its prominent role in inflammation, immune responses and cancer, the C-X-C chemokine receptor type 4 (CXCR4) has gained significant attention in recent years and has become a relevant target in drug development. Although the signaling properties of CXCR4 have been extensively studied, several aspects deserve deeper investigations. Mutations in the C-term tail of the CXCR4 gene cause WHIM syndrome, a rare congenital immunodeficiency associated by chronic leukopenia. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 81 publications
(110 reference statements)
2
11
0
Order By: Relevance
“…To date, all the twelve known heterozygous gain-of-function CXCR4 WHIM mutations are in the genomic region that encodes the C-terminal domain of the receptor ( Figure 1A ). And c.1000C> T (p. Arg334Ter, also written informally as R334X) is the most frequent ( Figure 1B ), which is consistent with a previous review ( 18 , 19 ). The nucleotide changes, mutation types, amino acid changes and the proportion of WHIM patients with CXCR4 mutation are also summarized ( Figure 1B ) ( 17 ).…”
Section: Introductionsupporting
confidence: 87%
“…To date, all the twelve known heterozygous gain-of-function CXCR4 WHIM mutations are in the genomic region that encodes the C-terminal domain of the receptor ( Figure 1A ). And c.1000C> T (p. Arg334Ter, also written informally as R334X) is the most frequent ( Figure 1B ), which is consistent with a previous review ( 18 , 19 ). The nucleotide changes, mutation types, amino acid changes and the proportion of WHIM patients with CXCR4 mutation are also summarized ( Figure 1B ) ( 17 ).…”
Section: Introductionsupporting
confidence: 87%
“…A small case-control gene-panel sequencing study of sporadic CLL included CXCR4, and identified a common variant in CXCR4 (rs2228014, MAF = 0.04) that was increased in CLL cases (uncorrected P = 0.0015) [50] . The association of this variant with CLL was not replicated in a second, larger case-control study (P = 0.84) [51] . However, one rare truncating variant and one missense variant were observed in CXCR4 in two CLL cases with positive family history which was absent from controls (not statistically significant) [51] .…”
Section: Discussionmentioning
confidence: 84%
“…The association of this variant with CLL was not replicated in a second, larger case-control study (P = 0.84) [51] . However, one rare truncating variant and one missense variant were observed in CXCR4 in two CLL cases with positive family history which was absent from controls (not statistically significant) [51] .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Of note, some of the candidate genes underlie autosomal-dominant blood disorders characterized by aberrant HSPC function. Gain-of-function mutations in CXCR4 cause the Warts, Hypogammaglobulinemia, Immunodeficiency and Myelokathexis (WHIM) syndrome, marked by impaired egression of HSPCs and other white blood cells out of the bone marrow 23,24 . CEBPA mutations cause familial acute myeloid leukemia 25 .…”
Section: Genetic Overlap With Blood Disorders and Other Blood Cell Traitsmentioning
confidence: 99%